1988
DOI: 10.1002/jlb.43.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Adrenal Hormones, Hemodynamic Factors, and the Endotoxin-Related Stress Reaction to Stable Prostaglandin Analog-Induced Peripheral Lymphopenia and Neutrophilia

Abstract: Stable prostaglandin analogs are known to induce lymphopenia and neutrophilia in a dose-dependent fashion after subcutaneous injection in rats. The purpose of the present investigation is to determine whether the prostaglandin-induced changes in circulating leukocytes might be secondary to hypotension with the ensuing release of adrenal hormones. The adrenal medullary catecholamine epinephrine was found to induce neutrophilia in both intact and adrenalectomized rats, and the glucocorticosteroid analog dexameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…This is supported by the facts that adrenalectomy attenuates lymphopenia induced under stress [44,46], and that corticosterone causes lymphopenia in adrenalectomized rats [45,46]. Glucocorticoids seem to cause lymphopenia both in humans [47–49] and animals [44,45,50], whereas catecholamines induce lymphocytosis [34,49] and a marked increase of the number of blood NK cells [34,49,51] in humans. It has also been shown that the redistribution of human NK cells is caused via beta2‐adrenoceptor stimulation [34], and that the adhesion of human NK cells to cultured endothelium was down‐regulated by beta‐adrenoceptor stimulation [52].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is supported by the facts that adrenalectomy attenuates lymphopenia induced under stress [44,46], and that corticosterone causes lymphopenia in adrenalectomized rats [45,46]. Glucocorticoids seem to cause lymphopenia both in humans [47–49] and animals [44,45,50], whereas catecholamines induce lymphocytosis [34,49] and a marked increase of the number of blood NK cells [34,49,51] in humans. It has also been shown that the redistribution of human NK cells is caused via beta2‐adrenoceptor stimulation [34], and that the adhesion of human NK cells to cultured endothelium was down‐regulated by beta‐adrenoceptor stimulation [52].…”
Section: Discussionmentioning
confidence: 96%
“…It has also been shown that the redistribution of human NK cells is caused via beta2‐adrenoceptor stimulation [34], and that the adhesion of human NK cells to cultured endothelium was down‐regulated by beta‐adrenoceptor stimulation [52]. In contrast to these studies in humans, it was reported that epinephrine induces lymphopenia as well as neutrophilia in rats [50], although the effect of catecholamines on the redistribution of lymphocytes including NK cells has not been well investigated in animals yet.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Cyanoketone treatment, which virtually eliminates the corticosterone stress response, also virtually eliminates the stress‐induced decrease in blood lymphocyte numbers, and significantly enhances the stress‐induced increase in blood neutrophil numbers. 22 Several studies have shown that glucocorticoid treatment induces changes in leukocyte distribution in mice, 44‐47 guinea pigs, 48 rats, 22,49,50 rabbits, 51 and humans. 52‐54 It has been shown in rats that both adrenalectomy (which eliminates the corticosterone and epinephrine stress response) 21,22,35,55 or cyanoketone treatment (which eliminates only the corticosterone stress response), virtually eliminate the stress‐induced redistribution of blood leukocytes.…”
Section: Stress‐induced Changes In Leukocyte Numbers In the Bloodmentioning
confidence: 99%
“…Lymphocyte numbers in the bone marrow are increased. Both lymphocyte and neutrophil function is suppressed, as measured by concanavalin-A proliferation and reactive oxygen species production respectively (Ulich et al, 1988). Understanding of the complex effects that these agents have on the body could not be easily understood with in vitro models alone.…”
Section: Rodent Models For Immunosuppressionmentioning
confidence: 99%